(a+3)(a-2)=x

Simple and best practice solution for (a+3)(a-2)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (a+3)(a-2)=x equation:


Simplifying
(a + 3)(a + -2) = x

Reorder the terms:
(3 + a)(a + -2) = x

Reorder the terms:
(3 + a)(-2 + a) = x

Multiply (3 + a) * (-2 + a)
(3(-2 + a) + a(-2 + a)) = x
((-2 * 3 + a * 3) + a(-2 + a)) = x
((-6 + 3a) + a(-2 + a)) = x
(-6 + 3a + (-2 * a + a * a)) = x
(-6 + 3a + (-2a + a2)) = x

Combine like terms: 3a + -2a = 1a
(-6 + 1a + a2) = x

Solving
-6 + 1a + a2 = x

Solving for variable 'a'.

Combine like terms: x + -1x = 0
-6 + 1a + a2 + -1x = 0

The solution to this equation could not be determined.

See similar equations:

| M^2=m+9X+3 | | 3(n)-5=2(n) | | 3/8=x/50 | | -9/35//45/7 | | 3x+5y=168x-5y=28 | | -3.6+3n+5nx=0 | | 0x=33 | | w+1-4(-4w-1)=5(w-1) | | -1=9x-7 | | 5=9x-7 | | 5/2.5=x/2 | | 6(x-5)-6=-3+(-9x+9)+9x | | 2.3x=1.15 | | -6=9x-7 | | 6(x+5)-6=-3+(-9x+9)+9x | | 2x+10=3x+-15 | | h(-4)=2x^2+4 | | h(3)=2x^2+4 | | 1n(5x+3)=3.6 | | 42+x+y=180 | | h(-1)=2x^2+4 | | h(0)=2x^2+4 | | 3x+3y=x-2y | | -3z-9z=4/5 | | a^2-2ab+b^2+4a^2b^2=0 | | h(2b)=2x^2+4 | | 18x-24x=1/3 | | 7=-5x+10 | | 4=5d+14 | | 4x+16y=7x+y | | x^2-216= | | 5w+3+w= |

Equations solver categories